Road safety in Poland, the Czech Republic and Slovakia. Presentation of international research results - Jacek Dworzecki (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2019)
The safety of road users is one of the most important elements of the functioning of every society. The data published by the European Commission shows that on roads in the EU in 2017 was 25.3 thousand deaths occuried in road accidents. To reduce the number of road accident victims, threats in this area should be identified and appropriate solutions implemented. The article presents factors in traffic accidents, elements of human mentality which have a significant impact on driving a vehicle, factors influencing a driver’s action in traffic and correlation of the system of safety management including the procedure of risk management. The article presents partial results of international scientific research carried out in Poland, Czech Republic and Slovak Republic. In the survey participated respondents from ten cities. Opinions were obtained from 642 people on the subject of individual personality factors determine the behaviour of vehicle drivers. Furthermore were presented respondents´ answers regarding legal changes relating to the proposal penalties for drivers participating in road traffic under the influence of alcohol and drugs. The article has been prepared within the frames of realizing a research project called „Simulator supporting police officers’ training in the implementation of activities during a road accident” no. DOB-BIO9/06/01/2018, which has received funding from the Polish National Centre for Research and Development.